Income replacement in retirement: Longitudinal evidence from income tax records - Frank T. Denton; Ross Finnie; Byron G. Spencer (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2009)
We analyse a large longitudinal data file to determine who has retired and to assess how successful they are in maintaining their incomes after retirement. Our main conclusions are as follows. First, in the two years immediately after retirement the after-tax income replacement ratios average about two-thirds when calculated across all ages of retirement. Second, the ratios tend to increase with the age of retirement. Third, the ratios increase with years in retirement, at least in the first few years. Finally, income replacement ratios are highest in the lowest income quartile and generally decline as income increases; within each quartile the replacement ratios are higher for those who retired later than for those retired earlier.
Keywords: J26; D31; J14; 330; income replacement; retirement; Altersgrenze; Alterssicherung; Einkommen; Steuertarif; Kanada